A cryogenic machine for selective recovery of xenon from breathing system waste gases. - John Dingley (Anesthesia and Analgesia, 2008)
BACKGROUND:Xenon has many characteristics that make it very attractive as an anesthetic and therapeutic drug. Unfortunately, the supply of xenon is fixed, and therefore reclamation and recovery from even the most efficient breathing circuits is desirable. We built and evaluated a cryogenic device to recover xenon from waste anesthetic gases.METHODS:Xenon was selectively frozen to -139.2 degrees C from test gas mixtures at ambient pressure (STP). The machine ran on standard 240 V 13 A electrical current without refrigerants that required replenishing, e.g., liquid nitrogen. A wide range of xenon/oxygen mixtures were processed over a range of freezing chamber temperatures. Efflux gas and thawed reclaimed xenon were collected separately. Xenon purity and yield (fraction recovered) were measured and calculated on each occasion.RESULTS:Gas was processed at 300 mL/min, and the operating temperature was -139.2 (0.096) degrees C [Mean (sd)]. Purity and yield were >90% and >70% for gas mixtures containing > or =20% xenon, increasing to >95% and >85%, respectively, with an input gas xenon fraction > or =40%. Efficiency improved linearly with reducing temperature.CONCLUSIONS:Xenon of high purity (>90%) and yield (>70%) for such a machine was recovered from all gas mixtures containing > or =20% xenon. The operating temperature of the freezing chamber is a major influence on the efficiency of recovery.